Analysis of Sharia Hotel Standardization According to the Indonesian Council of Ulama (MUI) Fatwa at Arabia Style Hotel - Azura Rizti Saladin; Zuhrinal M Nawawi; Purnama Ramadani Silalahi (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
This study aims to analyze the standardization of sharia hotels based on the Indonesian Ulema Council (MUI) Fatwa No. 108/DSN-MUI/X/2016 using the Balanced Scorecard approach, focusing on Hotel Arabia Style in Medan. The Balanced Scorecard was employed to evaluate the hotel’s performance from four perspectives: internal business processes, learning and growth, customer, and financial. Data were collected through questionnaires distributed to 13 employees and 20 guests of the hotel. The findings reveal that: (1) From the internal business process perspective, the hotel has implemented several sharia principles but lacks sufficient sharia supervision and still utilizes conventional banking services; (2) The learning and growth perspective shows that while the hotel has policies ensuring staff adhere to Islamic dress codes, it has yet to establish a Sharia Supervisory Board within its organizational structure, with employee satisfaction reaching 89.6%; (3) The customer perspective indicates a high customer satisfaction rate of 90%, demonstrating that the hotel successfully meets customer expectations, particularly in providing services in line with Islamic values; and (4) The financial perspective shows positive results across various measured aspects. This study recommends enhancing sharia supervision and restructuring the financial operations to better align with sharia principles